2013
DOI: 10.1590/s0103-84782013005000098
|View full text |Cite
|
Sign up to set email alerts
|

Soybean silage and sugarcane tops silage on lamb performance

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
1
7
1
4
Order By: Relevance
“…However, the present study agrees with that of Zhang et al (2013), who reported reduced CP content with LD inoculation in Urtica cannabina silage. Other studies (Mustafa & Seguin, 2003;Lima et al, 2013;Touno et al, 2014) have recorded CP values in soybean silage that are higher than in the soybean silage of the present study, which might be attributed to the different soybean forage cultivars used amongst these studies. Inoculation did not affect EE contents in soybean silages of the present study (Table 3).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…However, the present study agrees with that of Zhang et al (2013), who reported reduced CP content with LD inoculation in Urtica cannabina silage. Other studies (Mustafa & Seguin, 2003;Lima et al, 2013;Touno et al, 2014) have recorded CP values in soybean silage that are higher than in the soybean silage of the present study, which might be attributed to the different soybean forage cultivars used amongst these studies. Inoculation did not affect EE contents in soybean silages of the present study (Table 3).…”
Section: Discussioncontrasting
confidence: 63%
“…This might be because of higher EE content in the Pannar cultivar before ensiling. The EE content in the Pannar soybean silage was higher than 42 g EE/kg DM reported in the literature (Tobia et al, 2008;Dias et al 2010;Lima et al, 2013). The relatively high EE content of soybean silage is an important feed parameter since it represents a high energy contribution to balanced animal feeds.…”
Section: Discussionmentioning
confidence: 73%
“…Evangelista et al (1991) examined the weight gain of steers fed diets containing soybean silage and registered that silage from corn-soybean intercropping (435 g animal day ). Lima et al (2013) evaluated the replacement of concentrate with soybean silage in diets with sugarcane silage for lambs and reported no differences in daily weight gain and feed conversion, with average values of 7.9 and 6.2 kg animal day -1 , respectively. Moreover, Souza et al (2014) studied the performance of beef cattle on diets with increasing levels of Stylosanthes cv.…”
Section: Resultsmentioning
confidence: 99%
“…inoculants are an option for improving fermentation profile and reducing losses during the fermentation process (Lima et al, 2013;Yokota et al, 1992). However, the effect of additives on animal performance has not been evidenced (Zopollatto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing of mature, standing sugarcane in commercial animal production systems is recommended only in an emergency (Pate et al 2002). Despite these issues, sugarcane tops and trash can be an effective source of roughage if supplemented with nitrogen (either as protein or as urea) (Pate et al 2002, Galina et al 2004, 2007, Karbhari et al 2007, Ortiz-Rubio et al 2008) and other nutrients (Gendley et al 2003, Sharma et al 2007, and are routinely used in both subsistence and commercial agriculture in Asia (Reddy and Prasad 1982a,b, Chen et al 1983, Baconawa 1986, Reddy et al 1992, Yuangklang et al 2005, Africa (Grieve 1976, Mahala et al 2013, South America (Thiago et al 1986, Bravo et al 1996, de Lima et al 2014, Oliveira and Millen 2014, and North America (Pate et al 2002).…”
Section: Tops and Trashmentioning
confidence: 99%